Monitoring heart rate derived indices and DC-potential of the brain over a 12-week endurance training period in recreational runners - Botella Ruiz, Javier (2015)
Purpose: The present study examined the agreement between HR-derived indices obtained over different recording situations (morning upon waking, in the lab, and during nocturnal measurements). Changes in DC-potential were examined following a high-intensity training (HIT) week by comparing them to a control week. Moreover, the relationship between adaptation to endurance training and the changes of morning HR-derived indices were examined. Methods: Eighteen subjects performed all testing and measurements (10 men, age 36.4 ± 6.1 yr; height 178.3 ± 5.2 cm; weight 77.8 ± 6.2 kg; VO2max 55.7 ± 6.0 ml/kg/min; 8 women, age 34.1 ± 7.5 yr; height 166.8 ± 6.7 cm; weight 61.7 ± 7.5 kg; VO2max 47.1 ± 4.8 ml/kg/min). During the 12-week period, daily DC-potential and HR-derived indices were obtained upon waking, together with nocturnal HR recordings. Endurance performance was assessed at three time points (PRE, MID, POST) via a 3km Time Trial (TT) and a VO2max test until exhaustion, with the analysis of maximal velocity (Vmax). Results: There was an acceptable agreement between the home and lab measurement for HR (ICC = .754), questionable agreement for Ln RMSSD (ICC = .647) and Ln HF (ICC = .575), and poor agreement for Ln LF (ICC = .427), Ln TP (ICC = .492), and DC-potential (ICC = .291). Agreement between nocturnal and morning measurements ranged from poor to questionable due to low ICC (range from .368 to .683), despite a small typical error. DC-potential did not change following a HIT training period (p>0.05). Weekly morning HR changes significantly correlated with changes in endurance performance over the 8-week intervention period. Conclusion: The lab measurements seem to moderately agree with home measurements for time-domain indices. The nocturnal and morning measurements agreement ranged from poor to moderate, thus being not recommended to compare results between these different methods. DC-potential was not affected by changes in training load as observed in HIT periods. Weekly morning HR seems to be the best index to use when evaluating adaptations to endurance training.